Thermomyces lanuginosus lipase immobilized on magnetic nanoparticles and its application in the hydrolysis of fish oil. Issue 5 (25th April 2018) - Matuoog, Naeema; Li, Kai; Yan, Yunjun
Abstract: This article describes the immobilization and stabilization of lipase from Thermomyces lanuginosus (TLL) onto magnetic nanoparticles, which led to a markedly improved performance of the enzyme. The optimal immobilization conditions were found to be a pH of 7.5, 40°C, 4 hr, and 4.4 mg TLL protein/g of support of lipase. These results were used to enrich the docosahexaenoic acid (DHA) which is used in the fields of medicine and food. When the immobilized lipase was utilized to enrich DHA, the DHA content increased with the increasing amount of enzyme up to 4.4 mg TLL protein/g of support of lipase. The water content also influenced the DHA content, with the highest DHA content at 50% water, 40°C, and a pH of 7 after 14 hr that is, 4.4‐fold the initial content of DHA fish oil for TLL‐GMNPs. After six cycles of successive usage, it still remained over 82% relative hydrolysis. Practical applications: One of the most important applications in use Omega 3, it is important for human health, industrial applications in the fields of food and medicine.